Improving crop productivity in sustainable agriculture - Tuteja, Narendra; Tuteja, Renu (Wiley-Blackwell, 2013)
An up-to-date overview of current progress in improving crop quality and quantity using modern methods. With a particular emphasis on genetic engineering, this text focusses on crop improvement under adverse conditions, paying special attention to such staple crops as rice, maize, and pulses